Validity of Questionnaire and Representativeness of Objective Methods for Measurements of Mechanical Exposures in Construction and Health Care Work. - Markus Koch; Lars-Kristian Lunde; Tonje Gjulem; Stein Knardahl; Kaj Bo Veiersted (PLoS ONE, 2016)
OBJECTIVES:To determine the criterion validity of a questionnaire on physical exposures compared to objective measurements at construction and health care sites and to examine exposure variation over several working days. METHODS:Five hundred ninety-four construction and health care workers answered a baseline questionnaire. The daily activities (standing, moving, sitting, number of steps), postures (inclination of the arm and the trunk), and relative heart rate of 125 participants were recorded continuously over 3-4 working days. At the end of the first measurement day, the participants answered a second questionnaire (workday questionnaire). RESULTS:All objective activity measurements had significant correlations to their respective questions. Among health care workers, there were no correlations between postures and relative heart rate and the baseline questionnaire. The questionnaires overestimated the exposure durations. The highest explained variance in the adjusted models with self-reported variables were found for objectively measured sitting (R2 = 0.559) and arm inclination > 60° (R2 = 0.420). Objective measurements over several days showed a higher reliability compared to single day measurements. CONCLUSIONS:Questionnaires cannot provide an accurate description of mechanical exposures. Objective measurements over several days are recommended in occupations with varying tasks.